Evaluation of clinically relevant landmarks of the marginal mandibular branch of the facial nerve: A three‐dimensional study with application to avoiding facial nerve palsy. Issue 2 (11th June 2015) - Davies, Joel C.; Ravichandiran, Mayoorendra; Agur, Anne M.; Fattah, Adel
Abstract : Injury to the marginal mandibular branch of the facial nerve (MMN) during surgery often results in poor functional and cosmetic outcomes. A line two finger breadths or 2 cm inferior to the border of the mandible is commonly used in planning neck incisions to avoid injury to the MMN. The purpose was to compare the two finger breadth/2 cm landmarks in predicting MMN course, and their accuracy/reliability. Thirty‐one cadaveric specimens were scanned to obtain 3D surface topography (FARO® scanner). Four independent raters pinned the inferior border of the mandible and a two finger breadth line and 2cm line below. The location of each pin was digitized (Microscribe™). A preauricular flap was raised, and MMN branches were digitized and modelled (Geomagic®/Maya®) enabling quantification of the accuracy of these landmarks. The location of the two‐finger breadth line was variable, spanning 25–51 mm below the inferior border of the mandible (ICC = 0.10). The most inferior MMN branch did not pass below the two‐finger breadth line in any specimen, but a narrow clearance zone (≤5 mm) was found in two. In contrast, in 7/31 specimens, the most inferior MMN branch coursed below the 2 cm line and would be at risk of injury. It was concluded that an incision two finger breadths below the inferior border of the mandible could provide safer access than the 2 cm line. After an incision has been placed using the two finger‐breadth landmark, caution must be exercised during dissection as branches of the MMN may lie only a few millimeters superior to the incision. Clin. Anat. 29:151–156, 2016. © 2015 Wiley Periodicals, Inc.